Molecular epidemiology of Animal African Trypanosomosis in southwest Burkina Faso. - Robert Eustache Hounyèmè; Jacques Kaboré; Geoffrey Gimonneau; Martin Bienvenu Somda; Ernest Salou; Antoine Abel Missihoun; Zakaria Bengaly; Vincent Jamonneau; Alain Boulangé (Public Library of Science (PLoS), 2022)
Background Animal African Trypanosomosis (AAT) is a parasitic disease of livestock that has a major socio-economic impact in the affected areas. It is caused by several species of uniflagellate extracellular protists of the genus Trypanosoma mainly transmitted by tsetse flies: T. congolense, T. vivax and T. brucei brucei. In Burkina Faso, AAT hampers the proper economic development of the southwestern part of the country, which is yet the best watered area particularly conducive to agriculture and animal production. It was therefore important to investigate the extent of the infection in order to better control the disease. The objective of the present study was to assess the prevalence of trypanosome infections and collect data on the presence of tsetse flies. Methods Buffy coat, Trypanosoma species-specific PCR, Indirect ELISA Trypanosoma sp and trypanolysis techniques were used on 1898 samples collected. An entomological survey was also carried out. Results The parasitological prevalence of AAT was 1.1%, and all observed parasites were T. vivax. In contrast, the molecular prevalence was 23%, of which T. vivax was predominant (89%) followed by T. congolense (12.3%) and T. brucei s.l. (7.3%) with a sizable proportion as mixed infections (9.1%). T. brucei gambiense, responsible of sleeping sickness in humans, was not detected. The serological prevalence reached 49.7%. Once again T. vivax predominated (77.2%), but followed by T. brucei (14.7%) and T. congolense (8.1%). Seven samples, from six cattle and one pig, were found positive by trypanolysis. The density per trap of Glossina tachinoides and G. palpalis gambiensis was 1.2 flies. Conclusions/significance Overall, our study showed a high prevalence of trypanosome infection in the area, pointing out an ongoing inadequacy of control measures.